Development of a Korean Liver Allocation System using Model for End Stage Liver Disease Scores: A Nationwide, Multicenter study - Lee, Juhan (Sci Rep, 2019)
The previous Korean liver allocation system was based on Child-Turcotte-Pugh scores, but increasing numbers of deceased donors created a pressing need to develop an equitable, objective allocation system based on model for end-stage liver disease scores (MELD scores). A nationwide, multicenter, retrospective cohort study of candidates registered for liver transplantation from January 2009 to December 2011 was conducted at 11 transplant centers. Classification and regression tree (CART) analysis was used to stratify MELD score ranges according to waitlist survival. Of the 2702 patients that registered for liver transplantation, 2248 chronic liver disease patients were eligible. CART analysis indicated several MELD scores significantly predicted waitlist survival. The 90-day waitlist survival rates of patients with MELD scores of 31–40, 21–30, and ≤20 were 16.2%, 64.1%, and 95.9%, respectively (P < 0.001). Furthermore, the 14-day waitlist survival rates of severely ill patients (MELD 31–40, n = 240) with MELD scores of 31–37 (n = 140) and 38–40 (n = 100) were 64% and 43.4%, respectively (P = 0.001). Among patients with MELD > 20, presence of HCC did not affect waitlist survival (P = 0.405). Considering the lack of donor organs and geographic disparities in Korea, we proposed the use of a national broader sharing of liver for the sickest patients (MELD ≥ 38) to reduce waitlist mortality. HCC patients with MELD ≤ 20 need additional MELD points to allow them equitable access to transplantation. Based on these results, the Korean Network for Organ Sharing implemented the MELD allocation system in 2016.